Spectrum and Clinical Characteristics of Renal Diseases in Ghanaian Adults: A 13-Year Retrospective Study - Perditer Okyere; Isaac Okyere; Richard Kobina Dadzie Ephraim; Joseph Attakorah; Charlotte Osafo; Bernard Arhin; Sarah Bachelle; Albert Abaka-Yawson (International Journal of Nephrology)
Background. Renal diseases over the years have become one of the leading causes of morbidity and mortality worldwide. In this study, we assessed the spectrum and clinical characteristics of Ghanaians with renal diseases at the nephrology unit of Komfo Anokye Teaching Hospital (KATH), Kumasi. Methods. This was a retrospective hospital-based study conducted at Komfo Anokye Teaching Hospital (KATH) from the years 2005 to 2017. A non-randomized sampling approach was used to include 1426 participants who were diagnosed with AKI, CKD, ESRD, and nephrotic syndrome at the nephrology unit of KATH during the years under review. All the 1426 patients were eligible for the study. Demographic characteristics as well as clinical data such as the kind of renal disease presentation, causes of the renal disease, and the treatment options were also obtained from their records. Results. Overall, 1009 of the total participants had CKD (70.76%), 295 participants had ESRD (20.69%), 72 participants had AKI (5.05%), and 50 participants had nephrotic syndrome (3.51%). Furthermore, 69 (23.4%) participants with ESRD were on dialysis whiles 6 (8.3) and 17 (1.7) participants with only AKI and CKD superimposed AKI, respectively, were on dialysis. 226 (76.6%) participants with ESRD were on conservative therapy. Hypertension emerged as the major cause of renal disease presentation (53.93%) with bilateral leg edema (13.46%) being the major complaint. There was a significant association between CKD and age (p≤0.001). Nephrotic syndrome also showed a significant association with age (p≤0.001). Conclusion. This study revealed that patients at the nephrology unit of KATH, Ghana, are mainly adults between ages 46–55. The clinical pattern of renal diseases is dominated by CKD and ESRD. We conclude that hypertension, chronic glomerulonephritis, diabetic nephropathy, and sepsis are the most common causes of renal diseases. The commonest clinical presentations are bilateral leg edema, palpitations, headache, breathlessness, dizziness, and vomiting. Early diagnosis and management of these conditions may prevent or delay the progress to end-stage renal disease.